2011
DOI: 10.1080/09670262.2011.552194
|View full text |Cite
|
Sign up to set email alerts
|

Grazer-induced toxin formation in dinoflagellates: a transcriptomic model study

Abstract: The cosmopolitan marine dinoflagellate Alexandrium minutum is known to produce toxins causing paralytic shellfish poisoning (PSP). As has recently been shown, this toxicity can be enhanced by the presence of certain copepod species. Inducible defences are known from a variety of marine organisms, but the associated transcriptomic changes have only been investigated in model angiosperms. Here, we use a microarray approach to investigate the changes in gene expression during the copepodprovoked induction of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…Although this study found that grazers induced toxin production in dinoflagellates and this is supported by several studies on grazing effect to the toxin production in dinoflagellates, two upregulated genes that could be annotated in this study are unlikely to be directly involved in PSP toxin synthesis [48,[58][59][60].…”
Section: Environmental Stresssupporting
confidence: 71%
“…Although this study found that grazers induced toxin production in dinoflagellates and this is supported by several studies on grazing effect to the toxin production in dinoflagellates, two upregulated genes that could be annotated in this study are unlikely to be directly involved in PSP toxin synthesis [48,[58][59][60].…”
Section: Environmental Stresssupporting
confidence: 71%
“…A treatment where algae have been acclimatized to grazers for at least two cell divisions can be included to achieve this. The presence of more than one grazer-induced response suggests that unbiased screening methods like transcriptomics, proteomics, and metabolomics may be useful complements to traditional methods in order to comprehend the full response of phytoplankton to grazer cues (Yang et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies investigated changes in the transcriptome of A. tamarense and A. minutum in cultures with elevated cell toxin quotas after exposure to such grazers (Wohlrab et al, 2010;Yang et al, 2011). The same microarray probes were used in these investigations as in the present study, either alone or as part of a larger set.…”
Section: Toxin-related Gene Expressionmentioning
confidence: 99%